Monitoring, evaluation, and learning: the key to building effective partnerships with government to improve maternal and child health in the Rakai and Kyotera Districts of Uganda - Sklar, Marc; Murokora, Daniel (Frontiers in Public Health, 2024)
This paper describes the development of the Babies and Mothers Alive (BAMA) Foundation, a Ugandan-led non-government organization with a goal to improve access to quality reproductive, maternal and newborn care services in the government health sector. Since 2015, BAMA has established fully engaged partnerships with four district governments and the Ministry of Health, initially partnering with 24 health centers and hospitals, we have now expanded our work to 60 health facilities serving a population of approximately one million people.In this article we describe the Monitoring, Evaluation and Learning (MEL) system that has guided success in program design and implementation and informed the expansion of our health system strengthening interventions over the past eight years, as we expanded both the scope and scale of our partnership model. Our program design and implementation strategies have been defined by community-based, integrated, MEL activities that engage district health leadership, health providers and facility staff, political, cultural, and faith-based leaders, as well as our beneficiaries. Quantitative and qualitative data collected over the past eight years, as well as baseline health surveys in our two new districts of implementation, are guiding the first stages of our transition to scale strategy. Our MEL process is dynamic, as we continue to identify critical needs, and through data sharing with all stakeholders design the most cost-effective and sustainable program interventions.We believe our model of an integrated process of evidenced-based learning that includes our partners, both in government and civil society, and our beneficiary communities is relevant to other locally-led, community-based organizations working to transform the quality of government health delivery systems.